2012
DOI: 10.1080/01635581.2012.667862
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Effects of Resveratrol: Modulation of Transcription Factors

Abstract: Resveratrol (3, 4', 5-trihydroxystilbene), a naturally-occurring phytoalexin readily available in the diet, is reported to possess both chemopreventive and chemotherapeutic activities in several cancers. However, despite the identification of numerous molecular targets, the underlying mechanisms involved in the anticancer activities of resveratrol are not completely understood. Resveratrol is postulated to function as a potential signaling pathway modulator and as such, is demonstrated to affect a multitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 87 publications
0
85
0
1
Order By: Relevance
“…Previous studies have reported that resveratrol exerted antitumor activities at various stages of tumor initiation, promotion and progression (Cimino et al, 2012;Stefanska et al, 2012;Whitlock et al, 2012), including in esophageal squamous cell carcinoma (Tang et al, 2013). However, the molecular mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that resveratrol exerted antitumor activities at various stages of tumor initiation, promotion and progression (Cimino et al, 2012;Stefanska et al, 2012;Whitlock et al, 2012), including in esophageal squamous cell carcinoma (Tang et al, 2013). However, the molecular mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…One well-known example of the stilbenes is resveratrol, and its antitumor activity has been intensively studied. Several in vivo and in vitro studies have shown that resveratrol inhibits the growth of cancer cells and effects various molecular targets associated with cancer progression such as the Wnt signaling pathway, nuclear factor-kappa B (NF-ÎșB), and the MAPK/ERK pathway in different types of cancer (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…One well-known example of the stilbenes is resveratrol, and its antitumor activity has been intensively studied. Several in vivo and in vitro studies have shown that resveratrol inhibits the growth of cancer cells and effects various molecular targets associated with cancer progression such as the Wnt signaling pathway, nuclear factor-kappa B (NF-ÎșB), and the MAPK/ERK pathway in different types of cancer (17,18).Previously, two novel stilbenes, cis-and trans-suffruticosol D, were extracted from the seeds of Paeonia (5). The two chemicals have similar structures as the mass fragmentation pattern of trans-suffruticosol D was very similar to cis-suffruticosol D, with cis-suffruticosol D varying only from trans-suffruticosol D in its olefinic hydrogen signal (Fig.…”
mentioning
confidence: 99%
“…Many studies have suggested that RES suppresses the growth of many cancer cells through multiple, intricate cellular signaling pathways, such as the STAT, NF-ÎșB and Wnt signaling pathways (Vang et al 2011;Aluyen et al 2012;Whitlock & Baek 2012). Some studies also reported that RES inhibits the EMT process in pancreatic cancer cells by inhibiting the PI-3 K/Akt pathway (Li et al 2013).…”
Section: Discussionmentioning
confidence: 99%